Bentuk dan Fungsi Gondang Buhun dalam Tradisi Ngarempug di Kasepuhan Ciptagelar/Gelaralam, Sukabumi - Wrahatnala, Bondet; Prihatmojo, Hernawan (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2025)
The Gondang Buhun art of Kasepuhan Ciptagelar/Gelaralam is an art in the tradition of the ngarempug procession. This research aims to find out what the Gondang Buhun art is according to the Kasepuhan Ciptagelar/Gelaralam society. The Kasepuhan Ciptagelar/Gelaralam society is a group of people with a rice culture. Data was obtained through direct observation and then interviews with figures who are considered credible and know about the art of Gondang Buhun. In addition, data is obtained through literature studies on gondang art and other related literature. Based on the results obtained, this study found the form and function of Gondang Buhun art in Kasepuhan Ciptagelar/Gelaralam related to life.